The evaluation of university research in Spain - Jorge Alonso, Ana (2016)
This article analyzes the current duopoly of the companies that manage the rankings of publications and how this dynamic affects the public university, in general, as well as the system of accreditation for faculty researcher in Spain. The critical reflection on the causes and consequences of this biased assessment model evidences collision between the political and academic imaginaries which promote hegemony of science over social sciences. In the same way, it reveals a geostrategic logic over representing scientific literature in English and a propensity for quantitative aspects in the global publishing trend.